1992
DOI: 10.1152/jappl.1992.72.1.116
|View full text |Cite
|
Sign up to set email alerts
|

Effects of inhaled oxygen (up to 40%) on periodic breathing and apnea in preterm infants

Abstract: To discover whether increases in inhaled O2 fraction (FIO2; up to 40%) decrease apnea via an increase in minute ventilation (VE) or a change in respiratory pattern, 15 preterm infants (birth weight 1,300 +/- 354 g, gestational age 29 +/- 2 wk, postnatal age 20 +/- 9 days) breathed 21, 25, 30, 35, and 40% O2 for 10 min in quiet sleep. A nosepiece and a flow-through system were used to measure ventilation. Alveolar PCO2, transcutaneous PO2, and sleep states were also assessed. All infants had periodic breathing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
22
0
1

Year Published

1994
1994
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(27 citation statements)
references
References 0 publications
4
22
0
1
Order By: Relevance
“…20,21 This latter mechanism may be mediated by increased nitric oxide release in brainstem regions subserving ventilation 22 and may account for the emergence of decreased breath-to-breath variability of minute ventilation. 4 Thus, our study confirms previous findings indicating that apnea of prematurity can be treated by increasing the Fio 2 . 1 The Fio 2 required to eliminate apnea, however, varies between studies.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…20,21 This latter mechanism may be mediated by increased nitric oxide release in brainstem regions subserving ventilation 22 and may account for the emergence of decreased breath-to-breath variability of minute ventilation. 4 Thus, our study confirms previous findings indicating that apnea of prematurity can be treated by increasing the Fio 2 . 1 The Fio 2 required to eliminate apnea, however, varies between studies.…”
Section: Discussionsupporting
confidence: 91%
“…In fact, a modest increase in inspired oxygen concentration decreased apnea and periodicity in preterm infants, not via an increase in alveolar ventilation but rather through a decrease in breath-to-breath variability. 4 The effect of SupOx on sleep in infants with chronic neonatal lung disease (CNLD) was also studied; SupOx increased rapid eye movement (REM) sleep and decreased REM arousal in patients with CNLD. 5 A later study, however, indicated that higher oxyhemoglobin saturations decreased sleep efficiency but did not modify REM sleep duration or arousal index.…”
mentioning
confidence: 99%
“…These findings corroborate our re cent observations, showing that the adminis tration of low inspired oxygen concentrations would make breathing regular without an in crease in minute ventilation. There was, how ever, a decrease in the variances of ventila tion, tidal volume, inspiratory and expiratory times [14], In the present study also, minute ventilation did not change appreciably, but variance of the measurements decreased.…”
Section: Discussionsupporting
confidence: 51%
“…For example, infants with minimal airways or airspace disease may have unstable oxyhemoglobin saturation because of periodic breathing (3)(4)(5). Furthermore, it is not clear how often unstable respiratory system mechanics are responsible for the apparent need for supplemental O 2 .…”
mentioning
confidence: 99%